Renal Drug Dosage Adjustment According to Estimated Creatinine Clearance in Hospitalized Patients With Heart Failure. (July 2016) - Altunbas, Gokhan; Yazıcı, Mehmet; Solak, Yalcin; Gul, Enes E.; Kayrak, Mehmet; Kaya, Zeynettin; Akilli, Hakan; Aribas, Alpay; Gaipov, Abduzhappar; Yazıcı, Raziye; Ozdemir, Kurtulus
Abstract : It is of clinical importance to determine creatinine clearance and adjust doses of prescribed drugs accordingly in patients with heart failure to prevent untoward effects. There is a scarcity of studies in the literature investigating this issue particularly in patients with heart failure, in whom many have impaired kidney function. The purpose of this study was to determine the degree of awareness of medication prescription as to creatinine clearance in patients hospitalized with heart failure. Patients hospitalized with a diagnosis of heart failure were retrospectively evaluated. Among screened charts, patients with left ventricular ejection fraction <40% and an estimated glomerular filtration rate (eGFR) of ⩽50 mL/min were included in the analysis. The medications and respective doses prescribed at discharge were recorded. Medications requiring renal dose adjustment were determined and evaluated for appropriate dosing according to eGFR. A total of 388 patients with concomitant heart failure and renal dysfunction were included in the study. The total number of prescribed medications was 2808 and 48.3% (1357 medications) required renal dose adjustment. Of the 1357 medications, 12.6% (171 medications) were found to be inappropriately prescribed according to eGFR. The most common inappropriately prescribed medications were famotidine, metformin, perindopril, and ramipril. A significant portion of medications used in heart failure requires dose adjustment. Our results showed that in a typical cohort of patients with heart failure, many drugs are prescribed at inappropriately high doses according to creatinine clearance. Awareness should be increased among physicians caring for patients with heart failure to prevent adverse events related to medications.